Preparation method of high-toughness magnesium-lithium alloy plate
The preparation of fine Si Al-27Si eutectic alloys through jet deposition and the first heating and then cooling rolling process was solved, and the problem of large grain size of Mg2Si phase in magnesium-lithium alloy was realized, and the preparation of high-strength and tough magnesium-lithium alloy sheets was improved. Its mechanical properties and formability.
Patent Information
- Application Number
- CN202411550307.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The grain size of the Mg2Si phase in magnesium lithium alloy is large, resulting in poor forming properties and it is difficult for conventional rolling processes to achieve high strength.
The fine Si of the Al-27Si eutectic alloy prepared by spray deposition is uniformly distributed, combined with the rolling process of heating first and then cooling, and the high-temperature annealing after cold rolling, adjust the microstructure, refine the grains, and improve the mechanical properties.
The resulting high-strength tough magnesium lithium alloy sheet has tensile strength of 280MPa~305MPa, and the elongation is 8%~16%, which significantly improves the comprehensive mechanical properties of the alloy and the application potential of high temperature and high strength.
Smart Images

Figure CN119194191A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a magnesium-lithium alloy plate. Background Art
[0002] Magnesium-lithium alloys show considerable application potential in the fields of transportation and aerospace due to their low density, excellent specific strength and outstanding electromagnetic interference shielding capabilities. When the Li content is in the range of 5.7wt% to 10.3wt%, a dual-phase (α-Mg+β-Li) microstructure will appear, which can effectively balance strength and ductility. Although magnesium-lithium alloys excel in lightweight and processability, their strength is generally not as good as traditional magnesium alloys, which to some extent limits their application potential in various fields.
[0003] Alloying is one of the important means to strengthen magnesium-lithium alloys. Rare earth elements such as Y and Ce or non-rare earth elements such as Zn, Al, and Si are often used in magnesium-lithium alloys to strengthen the matrix. Although the addition of rare earth elements has a significant strengthening effect, it will further increase the cost. Among the non-rare earth elements, Zn will form an unstable phase, and the strengthening effect is not stable. Al has excellent solid solution strengthening and second phase strengthening effects in the alloy, and Si can form a high-temperature stable Mg2Si phase with Mg, which has a positive effect on improving the performance of the alloy. However, by adding the Si element to the aluminum-silicon eutectic alloy obtained by traditional smelting, the Mg2Si phase formed has a larger grain size, which is not conducive to improving its performance. The coarse Mg2Si phase makes it impossible to effectively refine the grains, and the formability during deformation is poor.
[0004] Rolling forming is one of the key means to prepare magnesium-lithium alloy plates. It can further strengthen the alloy and play a decisive role in its microstructure and mechanical properties. In general research, magnesium-lithium dual-phase alloys usually use cooling rolling to improve their mechanical properties. However, cooling rolling has a natural aging softening effect, which makes its mechanical properties less improved and difficult to meet high strength and toughness requirements. Summary of the invention
[0005] The present invention aims to solve the technical problem that the Mg2Si phase in the existing magnesium-lithium alloy has a large grain size and poor formability, and the magnesium-lithium alloy plate prepared by conventional rolling process is difficult to achieve high strength and toughness, and provides a method for preparing a high-strength and tough magnesium-lithium alloy plate.
[0006] The preparation method of the high-strength and toughness magnesium-lithium alloy plate of the present invention is carried out according to the following steps:
[0007] 1. Raw material preparation: Prepare raw materials according to the following mass percentages of each element: Li: 7.8-8.2wt.%, Al: 2.7-3.2wt.%, Si: 0.3-0.4wt.%, and the rest is Mg; the raw materials are magnesium blocks, aluminum blocks, lithium particles and Al-27Si eutectic alloy, and the Al-27Si eutectic alloy is prepared by spray deposition; the magnesium blocks, aluminum blocks and Al-27Si eutectic alloy are polished;
[0008] 2. Melting alloy ingot: put the raw materials prepared in step 1 into a vacuum furnace, evacuate, and then introduce a mixed gas of SF6 and Ar to a pressure of 0.013MPa~0.015MPa, heat to 450℃~455℃, the paraffin attached to the surface of lithium will volatilize and emit white smoke, stop heating after volatilization for 10min~11min, start evacuation, and raise the temperature to 680℃~690℃ when it is clearly visible in the furnace, and after the alloy is completely melted, lower the stirring paddle below the alloy liquid level, stir at a speed of 250rpm~300rpm for 3min~5min, stop stirring, keep warm at 680℃~690℃ for 10min~12min, raise the stirring paddle above the liquid level, cast the alloy liquid into the mold below, and then cool it to room temperature with the furnace to obtain an alloy ingot of 60mm×60mm×200mm; the mold is also located in the vacuum furnace;
[0009] 3. Preparation before rolling: The alloy ingot obtained in step 2 is cut into thin plates of 60 mm × 60 mm × 5 mm using an electric spark wire cutting machine, and then the surface is polished with coarse sandpaper, and then the cut alloy thin plates are kept in a muffle furnace at 200°C to 210°C for 20min to 25min;
[0010] 4. Rolling and annealing: Control the temperature of the rollers to be maintained at 120°C to 130°C, and the linear speed of the rollers to be maintained at 5m / min to 8m / min; quickly transfer the magnesium-lithium alloy sheet sample after the insulation treatment in step 3 to a twin-roll mill for rolling:
[0011] ①, the first pass is rolled at 200℃~210℃, the deformation is 10%; then roll after keeping at 200℃~210℃ for 10min~12min, the deformation is 20%;
[0012] ②, then keep at 250℃~260℃ for 10min and then roll, the deformation is 20%;
[0013] ③、Repeat the operation of ② again;
[0014] ④, keep warm at 300℃~310℃ for 10min and then roll, the deformation is 20%;
[0015] ⑤. Repeat step ④ again;
[0016] ⑥ The last 6 passes are rolled at room temperature with a deformation of 30%;
[0017] ⑦. Finally, annealing is performed at 240°C to 320°C for 1h to 1.5h to obtain a magnesium-lithium alloy sheet.
[0018] The Al-27Si eutectic alloy described in step 1 of the present invention is purchased from Jiangsu Haoran Spray Forming Alloy Co., Ltd., with the brand name of Al-27Si.
[0019] The present invention has the following advantages:
[0020] (1) In the present invention, Al-27Si eutectic alloy formed by spray deposition is added during the smelting process. In the Al-27Si eutectic alloy prepared by spray deposition, fine primary Si is evenly dispersed in the Al matrix, ensuring that the size of Si introduced into the eutectic alloy during the smelting process is not very large, so that the generated Mg2Si phase is fine (about 5 μm) and evenly distributed; the introduction of the fine Mg2Si phase is conducive to obtaining a fine-grained structure and better formability, and the Mg2Si phase has the characteristics of high melting point, high hardness and high-temperature stability, thereby improving the application potential of the alloy in high-temperature and high-strength environments;
[0021] (2) In the present invention, in step 4, a high-density dislocation is introduced through a rolling process of first heating and then cooling, thereby adjusting the microstructure of the magnesium-lithium alloy, refining the second phase particles, and generating a large number of fine recrystallized grains, thereby refining the grains and improving the mechanical properties of the magnesium-lithium alloy;
[0022] (3) The present invention adopts high temperature annealing after cold rolling to reduce dislocation density, increase the recrystallization volume fraction and grain size, and increase the volume fraction of the precipitated phase, thereby providing a sufficient second phase strengthening effect for the magnesium-lithium alloy and significantly improving the comprehensive mechanical properties of the magnesium-lithium alloy;
[0023] (4) The high-strength and toughness dual-phase magnesium-lithium alloy plate prepared by the present invention has a tensile strength of 280MPa to 305MPa and an elongation of 8% to 16%. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a physical photo of the magnesium-lithium alloy plate obtained in Experiment 2;
[0025] Figure 2 It is the SEM image of the products of ⑥ and ⑦ in step 4 of experiment 2;
[0026] Figure 3 This is a comparison chart of the effects of different annealing temperatures on the mechanical properties of the plate in experiments one to three. DETAILED DESCRIPTION
[0027] Specific implementation method 1: This implementation method is a method for preparing a high-strength and tough magnesium-lithium alloy plate, which is specifically carried out according to the following steps:
[0028] 1. Raw material preparation: Prepare raw materials according to the following mass percentages of each element: Li: 7.8-8.2wt.%, Al: 2.7-3.2wt.%, Si: 0.3-0.4wt.%, and the rest is Mg; the raw materials are magnesium blocks, aluminum blocks, lithium particles and Al-27Si eutectic alloy, and the Al-27Si eutectic alloy is prepared by spray deposition; the magnesium blocks, aluminum blocks and Al-27Si eutectic alloy are polished;
[0029] 2. Melting alloy ingot: put the raw materials prepared in step 1 into a vacuum furnace, evacuate, and then introduce a mixed gas of SF6 and Ar to a pressure of 0.013MPa~0.015MPa, heat to 450℃~455℃, the paraffin attached to the surface of lithium will volatilize and emit white smoke, stop heating after volatilization for 10min~11min, start evacuation, and raise the temperature to 680℃~690℃ when it is clearly visible in the furnace, and after the alloy is completely melted, lower the stirring paddle below the alloy liquid level, stir at a speed of 250rpm~300rpm for 3min~5min, stop stirring, keep warm at 680℃~690℃ for 10min~12min, raise the stirring paddle above the liquid level, cast the alloy liquid into the mold below, and then cool it to room temperature with the furnace to obtain an alloy ingot of 60mm×60mm×200mm; the mold is also located in the vacuum furnace;
[0030] 3. Preparation before rolling: The alloy ingot obtained in step 2 is cut into thin plates of 60 mm × 60 mm × 5 mm using an electric spark wire cutting machine, and then the surface is polished with coarse sandpaper, and then the cut alloy thin plates are kept in a muffle furnace at 200°C to 210°C for 20min to 25min;
[0031] 4. Rolling and annealing: Control the temperature of the rollers to be maintained at 120°C to 130°C, and the linear speed of the rollers to be maintained at 5m / min to 8m / min; quickly transfer the magnesium-lithium alloy sheet sample after the insulation treatment in step 3 to a twin-roll mill for rolling:
[0032] ①, the first pass is rolled at 200℃~210℃, the deformation is 10%; then roll after keeping at 200℃~210℃ for 10min~12min, the deformation is 20%;
[0033] ②, then keep at 250℃~260℃ for 10min and then roll, the deformation is 20%;
[0034] ③、Repeat the operation of ② again;
[0035] ④, keep warm at 300℃~310℃ for 10min and then roll, the deformation is 20%;
[0036] ⑤. Repeat step ④ again;
[0037] ⑥ The last 6 passes are rolled at room temperature with a deformation of 30%;
[0038] ⑦. Finally, annealing is performed at 240°C to 320°C for 1h to 1.5h to obtain a magnesium-lithium alloy sheet.
[0039] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the purity of the magnesium block, aluminum block and lithium particles in step 1 all reaches 99.9%. The rest is the same as the specific implementation method 1.
[0040] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the volume ratio of SF6 and Ar in step 2 is (4-5): (45-46). Other aspects are the same as specific implementation method 1 or 2.
[0041] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 3, the cut alloy sheet is kept in a muffle furnace at 200° C. for 20 minutes. The rest is the same as specific embodiments 1 to 3.
[0042] Specific implementation example 5: This implementation example is different from specific implementation example 4 in that: in step 4, the temperature of the roller is controlled to be maintained at 120° C., and the linear speed of the roller is maintained at 5 m / min. The rest is the same as specific implementation example 4.
[0043] Specific implementation method 6: This implementation method is different from specific implementation method 5 in that: in step 4, ①, the first pass is rolled at 200°C with a deformation of 10%; then the rolling is carried out after keeping at 200°C for 10 minutes with a deformation of 20%;
[0044] ②, then keep at 250℃ for 10min and then roll again, with a deformation of 20%;
[0045] ③、Repeat the operation of ② again;
[0046] ④. Keep at 300℃ for 10 minutes and then roll again, with a deformation of 20%.
[0047] The rest is the same as the fifth specific implementation method.
[0048] Specific embodiment 7: This embodiment is different from specific embodiment 6 in that: Step 4 ⑦, finally annealing is performed at 240°C to 320°C for 1 hour to obtain a magnesium-lithium alloy sheet. The rest is the same as specific embodiment 6.
[0049] The present invention is verified by the following tests:
[0050] Test 1: This test is a method for preparing a high-strength and tough magnesium-lithium alloy sheet, which is specifically carried out in the following steps:
[0051] 1. Raw material preparation: Prepare raw materials according to the following mass percentages of each element: Li: 8wt.%, Al: 3wt.%, Si: 0.3wt.%, and the rest is Mg; the raw materials are magnesium block, aluminum block, lithium particles and Al-27Si eutectic alloy, the Al-27Si eutectic alloy is prepared by spray deposition and purchased from Jiangsu Haoran Spray Forming Alloy Co., Ltd., with the brand name of Al-27Si; grind the magnesium block, aluminum block and Al-27Si eutectic alloy;
[0052] The purity of the magnesium block, aluminum block and lithium particles all reaches 99.9%;
[0053] 2. Melting alloy ingot: put the raw materials prepared in step 1 into a vacuum furnace, evacuate, and then introduce a mixed gas of SF6 and Ar to a pressure of 0.013MPa, raise the temperature to 450°C, the paraffin attached to the surface of lithium will evaporate and emit white smoke, stop heating after evaporation for 10 minutes, start evacuation, and raise the temperature to 680°C when it is clearly visible in the furnace. After the alloy is completely melted, lower the stirring paddle below the alloy liquid level, stir at a speed of 250rpm for 3 minutes, stop stirring, keep warm at 680°C for 10 minutes, raise the stirring paddle above the liquid level, cast the alloy liquid into the mold below, and then cool it to room temperature with the furnace to obtain an alloy ingot of 60mm×60mm×200mm; the mold is also located in the vacuum furnace; the volume ratio of SF6 and Ar is 1:9;
[0054] 3. Preparation before rolling: The alloy ingot obtained in step 2 is cut into thin plates of 60 mm × 60 mm × 5 mm using an electric spark wire cutting machine, and then the surface is polished with coarse sandpaper, and then the cut alloy thin plates are kept in a muffle furnace at 200 ° C for 20 minutes;
[0055] 4. Rolling and annealing: The temperature of the rolling rollers is controlled to be maintained at 120°C and the linear speed of the rolling rollers is maintained at 5m / min; the magnesium-lithium alloy sheet sample after the insulation treatment in step 3 is quickly transferred to a twin-roll mill for rolling:
[0056] ① The first pass is rolled at 200℃ with a deformation of 10%; then rolled at 200℃ for 10 minutes with a deformation of 20%;
[0057] ②, then keep at 250℃ for 10min and then roll again, with a deformation of 20%;
[0058] ③、Repeat the operation of ② again;
[0059] ④, after keeping at 300℃ for 10min, rolling again, the deformation is 20%;
[0060] ⑤. Repeat step ④ again;
[0061] ⑥ The last 6 passes are rolled at room temperature with a deformation of 30%;
[0062] ⑦. Finally, annealing was carried out at 320°C for 1 hour to obtain a magnesium-lithium alloy sheet with a thickness of 1 mm, a room temperature tensile strength of 303 MPa, and an elongation of 8%.
[0063] Experiment 2: The difference between this experiment and Experiment 1 is that in step 4⑦, annealing is finally carried out at 280°C for 1h to obtain a magnesium-lithium alloy sheet with a thickness of 1mm, and its room temperature tensile strength is 292MPa and the elongation is 14%.
[0064] Figure 1 This is a real photo of the magnesium-lithium alloy plate obtained in Experiment 2. It can be seen that the surface quality of the alloy material is good after rolling, indicating that the rolling process is applicable.
[0065] Figure 2 This is the SEM image of the product of step ⑥ and ⑦ in step 4 of experiment 2, that is, the comparison before and after annealing. It can be seen from the figure that after cold rolling, both the α-Mg phase and the β-Li phase are elongated along the rolling direction, and a shear deformation band appears in the α-Mg phase, while no shear band is observed in the β-Li phase. The appearance of the shear deformation band is because the non-basal slip of magnesium is difficult to activate during low-temperature deformation, and the dislocation migration between adjacent grains is difficult. Therefore, the larger shear stress promotes the occurrence of shear deformation, and the β-Li phase has more slip systems. During the plastic deformation process, the β-Li phase slip system is easy to start and deformation is easier. After annealing, due to the effect of the interfacial tension, the α / β phase boundary changes from a straight interface to a corrugated interface. At this time, the α / β phase boundary is relatively smooth. Small β-Li phase grains begin to be observed inside the α-Mg phase, indicating that annealing promotes recrystallization and increases the grain size. The fine blocky Mg2Si phase (about 5μm) is evenly distributed in the α-Mg phase, further enhancing the mechanical properties of the alloy and improving the application potential of the alloy in high-temperature, high-strength environments. The plate undergoes recrystallization near the grain boundaries and phase interfaces of the original grains, and the internal stress is released, which leads to a decrease in strength. However, under high-temperature annealing conditions, the AlLi phase particles originally dispersed in the β-Li phase dissolve into the matrix, forming a supersaturated β-Li phase, such as Figure 2 As shown after annealing, the supersaturated β-Li phase increases the strength, resulting in the overall strength not being greatly reduced, but the plasticity being increased.
[0066] Experiment 3: The difference between this experiment and Experiment 1 is that in step 4⑦, annealing is finally carried out at 240°C for 1h to obtain a magnesium-lithium alloy sheet with a thickness of 1mm, a room temperature tensile strength of 282MPa, and an elongation of 16%.
[0067] The plates obtained from experiments 1 to 3 were subjected to tensile test and mechanical property analysis. Figure 3 The figure shows the influence of each annealing temperature on its mechanical properties. It can be seen from the figure that after annealing at 240℃ for 1h after cold rolling, the tensile strength is 282MPa and the elongation is 16%; with the increase of annealing temperature, its strength gradually increases and the plasticity gradually decreases. When the annealing temperature is increased to 320℃, the tensile strength is 303MPa and the elongation is 8%, and its strength is close to the strength after cold rolling.
[0068] The reasonable rolling process in the present invention ensures that the magnesium-lithium alloy will not produce defects such as microcracks during the hot rolling process. At the same time, the grains are further refined after large plastic deformation, which plays a key role in improving the alloy performance, thereby enabling the magnesium-lithium alloy plate in the present invention to exhibit good performance.
Claims
1. A method for preparing a high-strength and tough magnesium-lithium alloy sheet, characterized in that The preparation method of the high-strength and toughness magnesium-lithium alloy sheet is carried out according to the following steps:
1. Rolling plate preparation: ①, prepare raw materials according to the following mass percentages of each element: Li: 7.8-8.2wt.%, Al: 2.7-3.2wt.%, Si: 0.3-0.4wt.%, and the rest is Mg; the raw materials are magnesium blocks, aluminum blocks, lithium particles and Al-27Si eutectic alloy, and the Al-27Si eutectic alloy is prepared by spray deposition; ②, put the raw materials prepared in step 1 into a vacuum furnace, evacuate, then introduce a mixed gas of SF6 and Ar to a pressure of 0.013MPa~0.015MPa, raise the temperature to 680℃~690℃, and after the alloy is completely melted, stir the stirring paddle at a speed of 250rpm~300rpm for 3min~5min, then keep it at 680℃~690℃ for 10min~12min, and finally cast to obtain an alloy ingot of 60mm×60mm×200mm; ③. Cut the alloy ingot obtained in step ② into thin plates of 60 mm × 60 mm × 5 mm, then polish the surface with coarse sandpaper, and then keep the alloy thin plates in a muffle furnace at 200° C. to 210° C. for 20 min to 25 min; 2. Rolling and annealing: Control the temperature of the rollers to be maintained at 120°C to 130°C, and the linear speed of the rollers to be maintained at 5m / min to 8m / min; quickly transfer the magnesium-lithium alloy sheet sample after the insulation treatment in step 1 to a twin-roll mill for rolling: ① The first pass is rolled at 200℃~210℃, with a deformation of 10%; then rolled after keeping at 200℃~210℃ for 10min~12min, with a deformation of 20%; ②, then keep at 250℃~260℃ for 10min and then roll, the deformation is 20%; ③、Repeat the operation of ② again; ④, keep warm at 300℃~310℃ for 10min and then roll, the deformation is 20%; ⑤. Repeat step ④ again; ⑥ The last pass is rolled at room temperature with a deformation of 30%; ⑦. Finally, annealing is performed at 240°C to 320°C for 1h to 1.5h to obtain a magnesium-lithium alloy sheet.
2. The method for preparing a high-strength and tough magnesium-lithium alloy sheet according to claim 1, characterized in that The purity of the magnesium block, aluminum block and lithium particles described in step 1① all reaches 99.9%.
3. The method for preparing a high-strength and tough magnesium-lithium alloy sheet according to claim 1, characterized in that The volume ratio of SF6 and Ar described in step 1② is (4~5):(45~46).
4. The method for preparing a high-strength and tough magnesium-lithium alloy sheet according to claim 1, characterized in that In step 1③, the cut alloy sheet is kept in a muffle furnace at 200°C for 20 minutes.
5. The method for preparing a high-strength and tough magnesium-lithium alloy sheet according to claim 1, characterized in that In step 2, the temperature of the roller is controlled to be maintained at 120° C., and the linear speed of the roller is maintained at 5 m / min.
6. The method for preparing a high-strength and tough magnesium-lithium alloy sheet according to claim 1, characterized in that In step 2, ①, the first pass is rolled at 200°C with a deformation of 10%; then, the roll is kept at 200°C for 10 minutes with a deformation of 20%; ②, then keep at 250℃ for 10min and then roll again, with a deformation of 20%; ③、Repeat the operation of ② again; ④, after keeping at 300℃ for 10min, rolling again, the deformation is 20%; ⑤. Repeat step ④ again; ⑥ The last pass is rolled at room temperature with a deformation of 30%.
7. The method for preparing a high-strength and tough magnesium-lithium alloy sheet according to claim 1, characterized in that Step 2⑦: finally annealing at 240°C to 320°C for 1h to obtain a magnesium-lithium alloy sheet.
Citation Information
Patent Citations
Preparation method of magnesium-lithium-aluminum-silicon alloy plate
CN103602861A
Modification treatment method of magnesium alloy die casting
CN111424201A
As-cast high-toughness fine-grain magnesium-lithium dual-phase alloy and resistance heating type preparation method thereof
CN117144214A
Mg Alloys Containing Misch Metal Manufacturing Method of Wrought Mg Alloys Containing Misch Metal, and Wrought Mg Alloys Thereby
US20080138236A1
